SENI MAJEJAITAN DAN METANDING SEBAGAI ATRAKSI WISATA DI ERA NEW NORMAL - Ida Ayu Tary Puspa; I Gusti Ngurah Pertu Agung; I Kadek Ananda Mertayasa (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2020)
Ceremonies and ceremonies in Hinduism have a special attraction for tourists visiting the island of Bali which is known as the Island of the Gods. Tourists want to have an authentic experience during their trip by joining the majejaitan and metanding program. With expressive emotions, a tourist village can package this majejaitan and metanding as a tourist attraction. This attraction has an artistic function in the form of satisfying human emotions and desires as well as a religious function where this attraction has extraordinary uniqueness so that it will be able to increase insight in connecting with God in a simple way.In this new normal era, even though the Covid-19 pandemic has not yet passed, tourist villages hasnot been able to do much to receive tourist visits, but in the future thistourist attraction can be packaged of course while promoting cleanliness, health and safety. CHS is the new standard of Tourism.